An Introduction to Florida commodity enterprise budgets: An Extension tool to improve farm financial planning - Kimberly L. Morgan; Tara Wade; Kevin Athearn; Chris Prevatt; Ariel Singerman; Edward Evans; Trent Blare; Hayk Khachatryan; Zhengfei Guan (EDIS)
Enterprise budgets help farmers and ranchers estimate expenses, potential revenue, and profit. UF/IFAS provides enterprise budgets for a variety of Florida-grown commodities. These are typically built collaboratively by economists, horticulturists and agronomists, ranchers, and growers. This publication highlights key aspects of the enterprise budget as a planning tool for farm businesses. Includes links to UF/IFAS enterprise budgets and related documents specific to several Florida commodities.